Studies in the History of the English Language VI : Evidence and Method in Histories of English. - Adams, Michael (Topics in English Linguistics TiEL., 2015)
The relationships among data, evidence, and methodology in English historical linguistics are perennially vexed. This volume- which ranges chronologically from Old to Present-Day English and from manuscripts to corpora- challenges a wide variety of assumptions and practices and illustrates how diverse methods and approaches construct evidence for historical linguistic arguments from an increasingly large and diverse body of linguistic data.